Highly Flexible and Efficient All‐Polymer Solar Cells with High‐Viscosity Processing Polymer Additive toward Potential of Stretchable Devices. Issue 40 (4th September 2018) - Chen, Shanshan; Jung, Sungwoo; Cho, Hye Jin; Kim, Na‐Hyang; Jung, Seungon; Xu, Jianqiu; Oh, Jiyeon; Cho, Yongjoon; Kim, Hyeongwon; Lee, Byongkyu; An, Yujin; Zhang, Chunfeng; et al.
Abstract: Considering the potential applications of all‐polymer solar cells (all‐PSCs) as wearable power generators, there is an urgent need to develop photoactive layers that possess intrinsic mechanical endurance, while maintaining a high power‐conversion efficiency (PCE).Herein a strategy is demonstrated to simultaneously control the intercalation behavior and nanocrystallite size in the polymer–polymer blend by using a newly developed, high‐viscosity polymeric additive, poly(dimethylsiloxane‐ co ‐methyl phenethylsiloxane) (PDPS), into the TQ‐F:N2200 all‐PSC matrix. A mechanically robust 10wt% PDPS blend film with a great toughness was obtained. Our results provide a feasible route for producing high‐performance ductile all‐PSCs, which can potentially be used to realize stretchable all‐PSCs as a linchpin of next‐generation electronics. Abstract : A mechanically robust photoactive layer, namely 10PDPS is achieved, enabling not only a high PCE of 6.87 % in conventional all‐PSCs but also a reliable PCE of 5.60 % in graphene electrode‐based flexible devices, for which 90 % of its PCE is retained after 100 bending cycles at a bending radius of 3 mm.